2019
DOI: 10.1016/j.joep.2019.04.009
|View full text |Cite
|
Sign up to set email alerts
|

Contagion of pro- and anti-social behavior among peers and the role of social proximity

Abstract: This paper uses a novel experimental design to study the contagion of pro-and antisocial behavior and the role of social proximity among peers. Across systematic variations thereof, we find that antisocial behavior is generally more contagious than pro-social behavior. Surprisingly, we also find that social proximity amplifies the contagion of antisocial behavior more strongly than the contagion of pro-social behavior, and that antisocial individuals are most susceptible to behavioral contagion of other antiso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
54
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 123 publications
(62 citation statements)
references
References 77 publications
7
54
0
1
Order By: Relevance
“…Finally, opportunistic conformity (the tendency to conform with selfish norms more than prosocial norms) has been observed in a number of previous studies in adults (Charness et al, 2019;Croson & Shang, 2008;Dimant, 2019) as well as in the adult sample analyzed here (see Section 9 in the Supplemental Material). However, we found that midadolescents displayed no signs of a directional asymmetry in social influence.…”
Section: Discussionmentioning
confidence: 52%
See 3 more Smart Citations
“…Finally, opportunistic conformity (the tendency to conform with selfish norms more than prosocial norms) has been observed in a number of previous studies in adults (Charness et al, 2019;Croson & Shang, 2008;Dimant, 2019) as well as in the adult sample analyzed here (see Section 9 in the Supplemental Material). However, we found that midadolescents displayed no signs of a directional asymmetry in social influence.…”
Section: Discussionmentioning
confidence: 52%
“…These conditions were included to potentially induce more prosocial or selfish behavior, respectively (Nook et al, 2016;Wei et al, 2016), and thus to assess possible age effects on opportunistic conformity (Charness et al, 2019;Croson & Shang, 2008;Dimant, 2019). Specifically, the observed donation was a random number in the relevant interval: observed donation ∈ [(donation 1 + 1), 45] for prosocial-influence trials and observed donation ∈ [(donation 1 -1), 5] for selfish-influence trials.…”
Section: Prosocial-influence Taskmentioning
confidence: 99%
See 2 more Smart Citations
“…A better understanding of how audiences shape status dynamics is important to mitigate the tension between achievement and ascription that is at the core of meritocratic evaluative settings-whereby audiences are supposed to justify their deliberations based on standards that can be articulated independently of available options [11]. In addition, understanding how audience evaluations may change with the degree of scrutiny to which they are amenable seems crucial in light of ever-increasing calls for transparency and fairness in public life [19]. It is therefore worthwhile to probe the interaction between candidates' status and audience-candidate connectivity, particularly if one considers that social proximity between producers and audience members is a constitutive feature of peer-based evaluative settings.…”
Section: Plos Onementioning
confidence: 99%